REVIEW: Endemic plants of serpentine soils - SUDARMONO SUDARMONO (Society for Indonesian Biodiversity, 2007)
Plant adaptation to serpentine soils is a system ideal for studies in evolutionary ecology. Serpentine soils are characterized by low calcium to magnesium ratios with Ca at significantly lower concentrations relative to surrounding areas. Although some variation occurs between sites which identified three collective traits: poor plant productivity, high rates of endemism and vegetation type distinct from those of neighboring areas. The several morphological feature characteristic of serpentine-tolerant species is possess xeromorphic foliage, including reduced leaf size and sclerophylls, the stature is significantly reduced relative to counterparts on non serpentine soil and root systems of species growing on and off serpentine sites are often more developed on serpentine soils than on neighboring soils. Serpentine soils are ubiquitous, but patchily distributed and thus promote geographic isolation. Adaptation to edaphic conditions may also begetreproductive isolation. Adaptive mutation might be influenced frequently from related species inhabiting surrounding areas. For the future studies involving serpentine systems merge the fields of ecology, evolution, physiology, and genetics required for serpentine adaptation.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: adaptive mutation, endemics, isolation, magnesium, serpentine